Restoring democratic governance in Zimbabwe: a critical investigation of the internet as a possible means of creating new sites of struggle for positive democratic change by Zimbabwean media and activists in Zimbabwe - Vennard, Francisca Caroline (Rhodes University, Faculty of Humanities, Department of Political Studies, 2002)
This thesis is a reaction to the state of utter lawlessness and the abuse of human rights by those in power in Zimbabwe over the past two years and it investigates the possibility of restoring democratic governance in that country by increasing the freedom of expression and media freedom, which is considered to be one of the most valuable elements in advancing democratization. Its aim is to establish the Internet as the best means possible to increasing media freedom and creating new 'sites of struggle' for activists in a context where the substantive freedom of expression does not exist. This in turn is shown to advance levels of democracy. To this end, the value of the freedom of expression to media freedom and the value of the latter to increasing levels of democracy is developed and the lack of democracy in Zimbabwe at all levels of society is considered. The Internet is seen to increase the freedoms of speech and association in new and interesting ways and it is discussed in various examples in which it has already been instrumental in evading the censorship of the media and increasing the ability of activists to express themselves freely and to organize more efficiently. Finally, the resources that Internet technology makes available to African journalists and activists are considered along with lessons gleaned from international examples of successful Internet use and it is shown to already be of use to Zimbabwean journalists and activists as they create to new cyberspaces in which they can struggle for positive democratic change in Zimbabwe. The Internet is also shown to have tremendous potential for future use in that country.
Keywords: Zimbabwe -- Politics and government -- 1980-; Internet in publicity; Press and politics -- Zimbabwe; Freedom of the press -- Zimbabwe; Digital media